Nectar Sugar Composition, Standing Nectar Crop and Floral Visitor Diversity of Three Endemic Plant Species from Western Ghats Biodiversity Hot‐Spot of India. Issue 6 (20th May 2022) - Pachpor, Tejaswini; Sonne, Mrunalini; Bhatt, Alap; Parkar, Kshitija; Shahane, Sneha; Mestry, Pratiksha; Kulkarni, Shivani; Ogale, Hemant; Patwardhan, Ankur
Abstract: Plant insect interactions are governed by various factors. Nectar availability and floral nectar composition play a significant role in deciding the pollinator pool that visits a particular plant species. This study investigates nectar sugar composition and volume from three endemic species from Western Ghats of India viz. Canthium dicoccum (Gaertn.) Teijsm. & Binn., Ligustrum perrottetii A. DC., and Wendlandia thyrsoidea (Roth) Steud., in their natural habitats. Our results demonstrate intraspecific variation in nectar sugar composition in these endemic plant species. Fructose, mannose and glucose sugars were found in the nectar of all three species. In addition to these three, arabinose was found in Ligustrum and sucrose in Canthium . Nectar volume showed variations in bagged and unbagged conditions. The highest average nectar quantity was found in Canthium (1.27 μl/flower), followed by Ligustrum (0. 31 μl/flower), and Wendlandia (0.14 μl/flower). Floral visitor diversity with a specific emphasis on butterflies showed the highest number of visitors on Ligustrum i. e., 42 out of 45 total butterfly species across all three plant species. This is the first report of standing nectar crop and nectar‐sugar composition data compiled for these plant species. Abstract :